DISTRIBUTION OF METALS IN CISANGGARUNG ESTUARY SEDIMENT, WEST JAVA, INDONESIA - Budiyanto, Fitri; Lestari, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2014)
Volcanic activities have inÃ¯Â¬â uenced the Cisanggarung estuary in western Cirebon Regency, altering metalÃÂ concentrations in the bottom sediment. Observation of metal content in the ocean there was carried out in AugustÃÂ 2009. Sediment samples were collected at 16 stations along the Cisanggarung coastline. The aim of this work wasÃÂ to determine the spatial distribution of Cd, Cu, Pb and Zn in the sediment of the Cisanggarung estuary. SedimentÃÂ was destructed using 3 acids: nitric acid, chloride acid and peroxide acid, which was then analyzed by Flame AtomicÃÂ Absorption Spectrophotometry based on the US EPA 3050b method. The highest concentrations of Cd, Cu, Pb andÃÂ Zn in the sediment were 0.73 mg/kg dry weight, 31.4 mg/kg dry weight, 23.9 mg/kg dry weight and 143 mg/kg dryÃÂ weight, respectively. The metals in the sediment had accumulated near the shoreline, up to Ã¯Â¬Â ve kilometers awayÃÂ from the river mouth, indicating that terrestrial area and sediment fractions inÃ¯Â¬â uenced their distribution.